Advanced graphics programming using openGL - McReynolds, Tom.; Blythe, David, 1961- (San Francisco, CA : Elsevier Morgan Kaufmann Publishers, 2005)
Today truly useful and interactive graphics are available on affordable computers. While hardware progress has been impressive, widespread gains in software expertise have come more slowly. Information about advanced techniquesbeyond those learned in introductory computer graphics textsis not as easy to come by as inexpensive hardware. This book brings the graphics programmer beyond the basics and introduces them to advanced knowledge that is hard to obtain outside of an intensive CG work environment. The book is about graphics techniquesthose that dont require esoteric hardware or custom graphics librariesthat are written in a comprehensive style and do useful things. It covers graphics that are not covered well in your old graphics textbook. But it also goes further, teaching you how to apply those techniques in real world applications, filling real world needs. * Emphasizes the algorithmic side of computer graphics, with a practical application focus, and provides usable techniques for real world problems. * Serves as an introduction to the techniques that are hard to obtain outside of an intensive computer graphics work environment. * Sophisticated and novel programming techniques are implemented in C using the OpenGL library, including coverage of color and lighting; texture mapping; blending and compositing; antialiasing; image processing; special effects; natural phenomena; artistic and non-photorealistic techniques, and many others. * Code fragments are used in the book, and full blown example programs for virtually every algorithm are available at www.mkp.com/opengl.
Part I Computer Graphics Intro and OpenGL: Concepts; Geometry Representation & Modeling; 3D Transformations; Color, Lighting, and Surface Attributes; Rasterization; Images as Primitives; OpenGL Virtues; Image Processing; Texture Mapping; Window System Integration; Hardware Implementations of the Pipeline. Part II Basic Techniques: Multiple Rendering Passes; Texture Mapping; Lighting; Blending and Compositing; Transparency; Antialiasing; Image Processing; Transform Techniques. Part III: Application Specific Techniques: CAD & Modeling; Scene Realism; Natural Phenomena; Special Effects; Illustration and Artistic Techniques; Scientific Visualization; Performance Measurement & Tuning; Visual Simulation and Entertainment. Appendices: Portability Considerations; OpenGL Extensions.
Includes bibliographical references (p. 615-627) and index.
Keywords: OpenGL; Computer graphics; Software; Electronic books